The role of women in the development of science and technology in the Third World - Faruqui, A. M. (Akhtar Mahmud); M. H. A. Hassan; Sandri, G. (Gabriella); The Third World Academy of Sciences (TWAS); Canadian International Development Agency (CIDA) (Singapore : World Scientific Pub., 1991)
32